Attitude towards foreign product purchase: Malaysian consumers' perspective - Shah K.A.M.; Ibrahim H.I.; Maludin N.; Ismail Z. (Inderscience Publishers, 2023)
The current research examined Malaysian consumers' attitudes towards foreign product purchase. Specifically, the study investigated the consumers' attitude, which is characterised by boycott, animosity, ethnocentrism, patriotism, and world- mindedness towards foreign made products. The study also examined how these constructs can affect consumers' foreign product judgment and willingness to purchase such products. In total, 512 responses were collected from the states of Penang, Kuala Lumpur, Melaka and Terengganu. The goodness of fit analysis and hypotheses testing were performed using SEM-PLS software. The findings exhibited that consumer patriotism and consumer world-mindedness mediated the relationship between product judgement and purchase willingness. The results also indicated that consumers with attitude of animosity and ethnocentrism negatively perceived foreign made products and consumers with world-mindedness attitude positively perceived foreign made products. As expected, only world-mindedness was positively related to purchase willingness. Finally, discussion for future direction and managerial implications are highlighted. Copyright 2021 Inderscience Enterprises Ltd.